Performance indicators of winning and defeated female handball teams in matches of the 2012 Olympic Games tournament - Milanovic, D.; Vuleta, D.; Ohnjec, K. (Journal of Human Kinetics, 2018)
The aim of the study was to determine performance indicators of winning and defeated women teams of the 2012 Olympic Games handball tournament. The sample of entities consisted of 27 games played during the preliminary round of the competition. The sample of variables consisted of the completed and unsuccessfully executed technical and tactical handball elements in attacking and defensive actions during handball matches (14 variables describing performance in attack and three variables related to defensive play). The differences between the winning and defeated teams in performance variables were determined using the Mann-Whitney U-test. The results showed statistically significant differences between the winning and defeated teams in the following variables: successful fast-break shots (5.11 ± 2.79 vs. 3.00 ± 1.88), unsuccessful wing shots (2.33 ± 1.24 vs. 3.67 ± 1.98), unsuccessful long-range shots (10.70 ± 3.98 vs. 13.37 ± 4.33), steals (5.48 ± 2.28 vs. 4.04 ± 2.07), and assists (13.81 ± 4.04 vs. 11.37 ± 3.59). The winning teams were better in the variables defining offensive performance effectiveness, especially with regard to successful performance of counter attacks; they also had higher efficiency of attacking actions with a strict selection of distance shots and wing shots, as well as a higher number of assists and steals.